ANGGARAN PENDIDIKAN DALAM PERSPEKTIF POLITIK - Maskuri Maskuri (LP2M Universitas Ibrahimy, 2013)
Now days, many who define politics as a conflict maker and the maker of split-causing differences, so that such an assumption makes politics as a taboo thing, and should be shunned. In fact, as weÂ know, that human beings are social creatures and cannot be separated from politics, therefore the philosophers, especially Muslim philosopher as Al-Ghozali, Ibn Khaldun, Ibn Taymiyya, Imam Al-Mawardi, as well as Hobes, Aristotle, Plato have provided definitions on politic as the dream of an ideal society formation, to repair a bad state to be a good one.Education, as one of the social institutions, cannot be separated from politics, especially when it comes to state policy, it will be known how the State's commitment to empower its community through education. Because how this country see education, especially in terms of budget policy becomes one of the nation's attention evidence on education. Indonesia, the history of its education budget has experienced ups and downs, and the last provision has been stated that the allocation of the education budget is 20% (twenty percent). However, how is the budget allocation commitment in practice? Is there a political nuances behind the education budget?